THE EFFECT OF SELF-ASSESMENT ON STUDENTS’ SELF-EFFICACY AND WRITING COMPETENCY - Mona Jiwandani; Lokita Purnamika Utami; Luh Gede Eka Wahyuni (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2021)
ABSTRACTIn this Covid 19 pandemic, learning should be done from distance through online learning. This study aims at investigating the effect of self-assessment on students’ self-efficacy and writing competency simultaneously and separately on online learning. To run this research, 52 eleventh grade students of SMAN 1 Sukasada in the academic year 2020/2021 were chosen as the samples. This research applied nonequivalent control group design in which there were two groups compared, namely: self-assessment and conventional assessment. The data of writing competency were collected by using performance test which were then scored by using analytical scoring rubric, meanwhile self-efficacy data were collected by using questionnaire. The collected data were then analyzed by using One Way MANOVA. This research discovered: (1) there is no significant effect of self-assessment on self-efficacy and writing competency simultaneously (p>0.05), (2) there is no significant effect of self-assessment on writing competency separately (p>0.05), and 3) there is no significant effect of self-assessment on self-efficacy separately (p<0.05).